2022
DOI: 10.4166/kjg.2022.050
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features of Hepatitis C Virus-related Acute-on-chronic Liver Failure in a Korean Population

Abstract: Background/Aims: Acute-on-chronic liver failure (ACLF) is a widely recognized concept in which acute decompensation (AD) in patients with cirrhosis results in organ failure and high short-term mortality. On the other hand, few studies reflecting the various etiologies of cirrhosis are available. This study examined the clinical features of patients with hepatitis C virus (HCV)-related ACLF. Methods: Between January 2005 and December 2018, 109 HCV-related cirrhosis patients hospitalized for AD (ascites, hepatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…DAAs may be effective for the prevention of development into ALF among patients with acute HCV infection [ 124 ]. In patients with HCV-related ACLF, compared to previous studies on hepatitis B virus-related ACLF and alcohol-related ACLF, the prevalence of liver failure was very low (17.1%), whereas that of kidney failure was very high (71.4%) [ 125 ]. DAAs may not be effective for all patients with HCV infection and ACLF [ 126 ].…”
Section: Hepatitis B Virus (Hbv) Reactivation In Patients Treated Wit...mentioning
confidence: 93%
See 1 more Smart Citation
“…DAAs may be effective for the prevention of development into ALF among patients with acute HCV infection [ 124 ]. In patients with HCV-related ACLF, compared to previous studies on hepatitis B virus-related ACLF and alcohol-related ACLF, the prevalence of liver failure was very low (17.1%), whereas that of kidney failure was very high (71.4%) [ 125 ]. DAAs may not be effective for all patients with HCV infection and ACLF [ 126 ].…”
Section: Hepatitis B Virus (Hbv) Reactivation In Patients Treated Wit...mentioning
confidence: 93%
“…DAAs may not be effective for all patients with HCV infection and ACLF [ 126 ]. In the DAA era, however, as HCV infection may occasionally be associated with ACLF, which could lead to poor survival [ 125 , 126 , 127 , 128 , 129 ], we also focused on HCV acute exacerbation and ALT flare in this article. Although there are several excellent reviews about acute exacerbation and alanine aminotransferase flare in HCV carrier patients [ 77 , 86 ], we added the recent literature and reports in this review.…”
Section: Hepatitis B Virus (Hbv) Reactivation In Patients Treated Wit...mentioning
confidence: 99%
“…The investigators usually observed a similar or even significantly higher proportion of GIB in AD without ACLF than with ACLF. 8,11,17,19,20,23,25,28,29 Reasons for this may be multi-factorial. On one hand, bleeding may occur in the early stages of cirrhosis decompensation, while organ functions are preserved.…”
Section: Bleeding As Precipitant Of Aclfmentioning
confidence: 99%
“…In a previous study, ACLF was diagnosed at admission in almost 20% of patients with portal hypertension bleeding. 16 In studies of patients with decompensated cirrhosis of predominantly alcoholic or hepatitis C virus (HCV) etiologies, the proportion ranged from 8.6 to 49.4%, [17][18][19][20][21][22][23][24] and from 7.3 to 35.7% in HBV-related cirrhosis (►Table 1). 17, [25][26][27][28] In all of To TIPS or Not to TIPS in High Risk of Variceal Rebleeding and ACLF Gu et al 193 these studies, due to their retrospective nature, GIB occurred concomitant with ACLF and not as a definite precipitant.…”
Section: Association Between Variceal Bleeding and Aclf Bleeding As P...mentioning
confidence: 99%